Mapping Strategy And Training Quality Development To Improve Graduate Competency At The Surabaya Job Training Center - Aminatu Nadhifa Alfiah (Journal of Studies in Academic, Humanities, Research, and Innovation, 2025)
This study is intended to examine strategies in mapping and improving the quality of training applied at the UPT Job Training Center (BLK) Surabaya in order to produce graduates who have competence and are ready to enter the world of work. The research uses a qualitative descriptive approach with data collection methods through direct observation, document review, and interviews. The findings show that BLK Surabaya conducts regular quality mapping by evaluating the curriculum, learning methods, instructor qualifications, and completeness of training facilities and infrastructure. Efforts to improve quality are also carried out through curriculum revisions that refer to SKKNI, strengthening instructor competencies, utilizing digital technology, and synergy with the industrial sector. Despite still facing obstacles such as limited training equipment and slow administrative processes, BLK Surabaya continues to innovate to maintain the quality and relevance of its training programs.